NECROTIZING GINGIVITIS: CASE REPORTS I (REVIEW OF THE LITERATURE) - V.I. Shynkevych (Український стоматологічний альманах)
The prevalence of the necrotizing periodontal diseases is not high, their importance is clear because they represent the most severe conditions associated with the dental biofilm, with very rapid tissue destruction. In addition to bacteria, the etiology of necrotizing periodontal disease includes numerous factors that alter the host response and predispose to these diseases, namely HIV infection, malnutrition, stress or tobacco smoking. The diagnostic features of the disease are characteristic, but the clinical presentation may vary among patients. Successful treatment of the disease depends on systemic and local therapy choice, but requires further diagnosis of pre-existing periodontal disease and its management, as well as the leading risk factors determination and their elimination. This paper attempts to describe the clinical diagnostic features and the current treatment options along with a suggested protocol for comprehensive management with case reports and a brief review.